MiR-197 Inhibitor Loaded AbCD133@MSNs@GNR Affects the Development of Prostate Cancer Through Targeting ITGAV - Ju, Guanqun; Zhu, Yingjian; Du, Tao; Cao, Wanli; Lin, Jianhai; Li, Chun; Xu, Dongliang; Wang, Zhijun (Frontiers in Cell and Developmental Biology, 2021)
Prostate cancer is one of the most important male malignant tumors, ranking the second in the mortality rate of all tumors, traditional treatment of prostate cancer has obvious side effects and high recurrence rate, which seriously affects the treatment effect. Prostate cancer therapy based on microRNA has been one of the hot spots in research of this field. Previous studies indicated that miR-197 plays an important role in the occurrence and development of prostate cancer, but the molecular mechanism of miR-197 in bone metastasis of prostate cancer has not been reported yet. Here, we verified that miR-197 was significantly overexpressed in the prostatic cancer tissues and prostatic cancer cells, and the miR-197 expression was significantly higher than normal prostatic cancer cells, then we verified that miR-197 effect the proliferation, invasion and metastasis of prostatic cancer cells through regulate the ITGAV expression, and results indicated that miR-197 inhibitor was a potential suppressor of prostatic cancer. In order to solve the problem of how microRNA enters cells and is easy to degrade in clinical application, we synthesized AbCD133@GNR@MSNs@miR-197 inhibitor drug carrier, 35.42 ug of miR-197 inhibitor can be loaded in 1mg of AbCD133@MSNs@GNR, the AbCD133@GNR@MSNs@miR-197 inhibitor has good photothermal properties and photothermal controlled release properties, CD133 antibody modified on the surface of nano drug carriers can help more drug carriers enter into PCSCs. The pharmacodynamic effect of AbCD133@GNR@MSNs@miR-197 inhibitor on PCSCs in vivo and in vitro which under near infrared radiation was studied, results showed that AbCD133@MSNs@GNR@miR-197 inhibitor prepared here can suppress the development of PCSCs and the growth of PCSCs solid tumor significantly, our study not only provides theoretical basis and for the clinical treatment of prostate cancer but also provides a research scheme of drug loading and photothermal controlled therapy for prostate treatment based on microRNA.